Not a choice, not a job : exposing the myths about prostitution and the global sex trade - Raymond, Janice G. (Potomac Books, 2013)
A generation ago, most people did not know how ubiquitous and grave human trafficking was. Now many people agree that the 35.7 billion business is an appalling violation of human rights. But when confronted with prostitution, many people experience an odd disconnect because prostitution is shrouded in myths, among them the claims that ôprostitution is inevitable, ö and ôprostitution is a job or service like any other.ö In Not a Choice, Not a Job, Janice Raymond challenges both the myths and their perpetrators. Raymond demonstrates that prostitution is not sex but sexual exploitation, and that.